Management of unicondylar tibial plateau fractures: a review. Issue 1 (12th November 2021) - Warren, Daniel; Domingue, Grayson; Riehl, John T.
Abstract : Unicondylar tibial plateau fracture (TPF) is a common orthopaedic injury. Although some are treated nonsurgically with excellent results, many are treated operatively to achieve improved patient outcomes. Commonly utilized surgical treatment options include open reduction internal fixation (ORIF) and percutaneous treatment which may include arthroscopic reduction internal fixation (ARIF). The most used classification remains the Schatzker fracture classification. This article presents a review of the epidemiology, relevant anatomy, biomechanics, clinical presentation, diagnosis, and management of tibial plateau fractures.